PROBLEMATIKA HUKUM TERKAIT ALIMONY BAGI MANTAN ISTERI PNS DITINJAU DARI PERSPEKTIF PLURALISME HUKUM DI INDONESIA - Putri, Dita Elvia Kusuma (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2023)
Alimony is compensation given by one spouse to the other spouse for post-divorce financial support, which aims to help the spouse, not punish the other spouse.. In terms of implementation, there are inconsistencies in the application of alimony to Muslim and non-Muslim civil servants. Meanwhile, in Decision Number 650/Pdt.G/2013/PA.Wtp and Decision Number 1051/Pdt.G/2018/PAJT the judge rejected the application of the ex-wife of a Muslim civil servant to obtain 1/3 of her ex-husband's salary. However, in Decision Number 4 / Pdt.G / 2016 / PN Sdw, for former Catholic civil servant wives, the judge granted the request for a 1/3 share of the ex-husband's salary. Thus, there is ambiguity in alimony regulations which causes inconsistencies in the application of law regarding alimony. Based on the description above, the formulation of the problem in this article is, firstly, the regulation regarding alimony from former civil servant husbands to ex-wives in the provisions of laws and regulations in Indonesia. Second, reformulation of alimony law for former civil servant wives as an embodiment of social justice. This research is legal research, using statute approach, conceptual approach and case approach. The findings in this research are 1) Regulations regarding alimony from former civil servant husbands to ex-wives in the provisions of laws and regulations in Indonesia, are regulated in Article 225 of the Civil Code, Article 149 jo. Article 158 KHI, and Article 8 Government Regulation Number 10 of 1983. 2) reformulation of alimony law for former civil servant wives as an embodiment of social justice, can be carried out by synchronizing the statutory regulations establishing laws relating to alimony for former civil servant wives, and setting sanctions for those who do not fulfill the provisions for providing maintenance for former civil servant wives